CIT: A credit‐based incentive tariff scheme with fraud‐traceability for smart grid. Issue 9 (12th November 2013) - Wen, Mi; Zhang, Kuan; Lei, Jingsheng; Liang, Xiaohui; Deng, Ruilong; Shen, Xuemin (Sherman)
Abstract: The growing peak‐hour power demand has invoked an urgency to increase the peak‐hour supply. Although smart grid has been envisioned as the next generation power system due to its two‐way communication of information and power, the peak‐hour power shortage problem still exists. In this paper, we propose a credit‐based incentive tariff (CIT) scheme with fraud‐traceability for smart grid. Specifically, the CIT encourages retail customers to sell the power generated by their renewable resources back to the grid during peak hours via giving additional incentive rate to them based on their credits. If a fraud is detected during the power transaction, the malicious customer's identity can be traced out and his or her credit can be correspondingly reduced. The security analysis shows that the CIT resists various security threats and makes the incentive tariff fair and more secure. The performance evaluation demonstrates that the CIT can dramatically increase the peak‐hour supply and reduce the peak‐to‐average power demand ratio by up to 7%. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : This paper propose a credit‐based incentive tariff (CIT) scheme with fraud‐traceability for smart grid. Specifically, the CIT encourages retail customers to sell the power generated by their renewable resources back to the grid during peak hours via giving additional incentive rate to them based on their credits. The security analysis shows that the CIT resists various security threats and makes the incentive tariff fair and more secure. The performance evaluation demonstrates that the CIT can dramatically increase the peak‐hour supply and reduce the peak‐to‐average power demand ratio by up to 7%.